Prevalence and Risk Factors of Iliac Screw Loosening After Adult Spinal Deformity Surgery. Issue 17 (1st September 2017) - Banno, Tomohiro; Hasegawa, Tomohiko; Yamato, Yu; Kobayashi, Sho; Togawa, Daisuke; Oe, Shin; Mihara, Yuki; Matsuyama, Yukihiro
Abstract : Study Design: A retrospective study. Objective: We investigated the prevalence of iliac screw loosening and determined risk factors after adult spinal deformity surgery. Summary of Background Data: Lumbosacral fixation is crucial to maintain optimal sagittal alignment. Iliac screws are commonly placed to provide protection for sacral pedicle screws. Radiolucent areas around the screws indicate fixation loss and pseudarthrosis. Methods: Seventy-two patients with adult spinal deformity (13 men, 59 women; mean age, 69.0 yr) who underwent spinal deformity surgeries using bilateral iliac screws with at least 2 years follow-up were studied. Iliac and S1 screw loosening were assessed by postoperative radiograph. The period of loosening appearance and the relations between loosening and the following items were investigated: (1) upper instrumented vertebra, (2) L5/S interbody fusion, (3) iliac screw placement, (4) spinopelvic parameters (T1 pelvic angle, sagittal vertical axis, pelvic tilt, pelvic incidence-lumbar lordosis [LL]). Oswestry Disability Index scores were obtained preoperatively and 2 years postoperatively. Results: Iliac and S1 screw loosening was found in 20 (27.8%) and 7 patients (9.7%), respectively. Iliac screw loosening appeared at 5.2 months (range, 3–12) on average. Compared with nonloosening, loosening had significantly higher upper thoracic fusion rates (above T6), lower L5/S interbody fusion rate, higher misplacement rate, and higher insufficient correction rate (PI-LL >10°). Oswestry Disability Index significantly improved in nonloosening, whereas no significant difference was observed in loosening. Multiple regression analysis showed that misplacement (odds ratio = 10.8) and insufficient correction (odds ratio = 7.5) affected loosening. Conclusion: Iliac screw loosening indicated instability of the lumbosacral junction, resulting in sagittal malalignment and poor outcomes. Accurate screw insertion and restoration of optimal LL were necessary to prevent complications. Level of Evidence: 4